Influence of limestone amendments on yield and frying quality of potatoes cv. Bicentenaria - Sifuentes Zorrila, Diana (2024)
The quality of potatoes for processing depends on varietal, environmental and crop management factors, and the consumption of potato products has increased.The objective of the research was to determine the effect of calcareous amendments on the production and frying quality of potatoes potato cv. Bicentenaria under high Andean conditions.  The research was carried out in the rural community of Canín at Checras district (Lima) altitude of 3880 masl. The climate of the locality is humid and cold, with an annual rainfall of 800 mm and acid soils (pH 5.0) of sandy-clay texture. Five liming treatments and a control without liming were applied to the soil (agricultural lime 500 kg ha-1 and carbonatite 500, 1000, 1500 and 2000 kg ha-1). Agronomic and biochemical characteristics of the tuber were evaluated and sensory analysis was performed for potato frying. Data were analyzed statistically and the Scott-Knott test was used to compare treatment means. Liming with carbonatite 1500 kg ha-1 statistically outperformed the other treatments in tuber weight and was similar to the control; treatment with carbonatite 1000 kg ha-1 had a greater effect on mean tuber weight. The treatments with agricultural lime or carbonatite significantly reduced (p <0.05) the glucose content in the tuber with respect to the control. Sensory tests were significant for liming treatments for chip color. Soil liming influenced some agronomic characteristics and biochemical parameters of the tuber, as well as the sensory evaluation of potato chips.